Children’s Rights and the European Union – Framework - Hrabar, Dubravka (Children’s Rights in Regional Human Rights Systems, 2024)
According to the Principle of conferral, the European Union has no competences over family law, including the regulation of children’s rights. Therefore, legally binding documents (Treaty on European Union, Treaty on the Functioning of the European Union, and the Charter of Fundamental Rights of the European Union) refer to (some) children’s rights and the principles of treatment of children at a generic level. This fact does not present a major obstacle because all the European Union Member States are parties to the Convention on the Rights of the Child and many other treaties that regulate children’s rights in greater detail. Non-binding documents appear in a frenzy and show an ambition to resolve many children’s problems typically observed in developed countries of the world, including those of the European Union. As their provisions often overlap and aim to achieve many objectives, the question arises as to the purposefulness of many soft law documents, such as strategies, guidelines, resolutions, communications, recommendations, and agendas. They reflect the significant and specific problems encountered by children in the European Union and indicate the need for children’s rights to be exercised. Moreover, they are a signal to adults, not only parents, to do more for the protection of children and their rights. However, it is unclear to what extent soft law can provide an answer to related issues, especially because, as a rule and ever more frequently, new “values” are introduced in the name of the alleged non-discrimination of children, such as gender ideology. The Member States of the European Union have no unified position on this issue.Keywords:  children’s rights, European Union, Treaty on European Union, Treaty on the Functioning of the European Union, Charter of Fundamental Rights of the European Union, soft law